Maintenance mud crab (scylla serrata) with different feeding Frequency - Juni Handayani; Iskandar Putra; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in March-May 2014 held at the Village Canang Dry, EnvironmentalXX, Village Sicanang, District of Medan Belawan, Medan, North Sumatra Province. The aim of thestudy was to determine the effect of feeding frequency on the growth and survival of mud crab (Scyllaserrata)The method used is the experiment with 3 treatments and 3 replications of feeding 2 times aday (P1); feeding 3 times a day (P2); feeding 4 times a day (P3). Data were analyzed using ANOVA(P <0.05). Test materials were used as much as 36 crabs were maintained with the battery systeminside a plastic basket with size of 45.5 x 33 x 17 cm3. Plastic basket is divided into 4 sections byplacing bamboo as a divider so that the basket contains 4 crabs. The results showed that feedingtrash fish produces growth weight 108 g, daily growth rate 1,55 %, the growth in length 1,91cm and a higher 1,42 cm, survival rate 100%.Keyword : mud crab, feeding frequency, and growth